Senyawa Alkoloid dari Ekstrak Aseton Daun Sambung Nyawa Gynura procumbens L. (GpL) - Darminto, .; Muharram, . (bionature, 2009)
These research aims to isolate and identify alkaloid compound in acetone extracts from sambung nyawa leafs Gynura procumbens L. This compound obtained trough keeping the plant and isolation. The isolation consists of extraction, fractionation, purification, and identification. The identification consists of melting point test, three phase system test, and Dragendorf test. The results of the research are: 90 mg of white crystal with the range of its melting point is 134-1360 C. The crystals indicate positively with Dragendorf test. These results indicate that the compound can be classified in the alkaloid compound. Â  Keywords: alkaloid, acetone, Gynura procumbens L.